Book Review: Ecological Jurisprudence: The Law of Nature and the Nature of Law PelizzonAlessandro, Ecological Jurisprudence: The Law of Nature and the Nature of Law . Singapore: Springer, 2025. 424 pp. $54.99 (HB). ISBN: 978-981-96-0172-1. - Zia Saylor (Environmental Values, 2025)
Background & aim: Primary biliary cholangitis (PBC) is a chronic cholestatic liver disease that can lead to increased morbidity and mortality. This study described real-world treatment patterns and clinical outcomes by line of treatment among patients with PBC in the US. Materials & methods: Adults (≥18 years) diagnosed with PBC on or after 1 January 17 were identified in the IQVIA PharMetrics ® Plus database and grouped into newly diagnosed, first-line (1L) and second-line or more (2L+) cohorts. Index date was initial PBC diagnosis or initiation of 1L or 2L therapy; follow-up continued until the earliest of end of continuous enrollment, death or data end. Time to treatment initiation, treatment discontinuation and negative clinical outcomes were assessed with Kaplan-Meier analysis. Results: The newly diagnosed, 1L and 2L+ cohorts included 1748, 1659 and 181 patients, respectively (average age at index: 52.7-54.5 years; female: 84.2-89.0%). Of the newly diagnosed cohort, 34.8% did not initiate PBC treatment within 1.5 years post-diagnosis. In the 1L cohort, median time from diagnosis to 1L initiation was 1.2 months; median time from 1L initiation to 1L discontinuation/2L initiation was nearly 5 years. In the 2L+ cohort, median time from 2L initiation to 2L discontinuation was approximately 4 years. In the untreated, 1L, and 2L+ cohorts, 18.9%, 14.4% and 19.3% of patients developed ≥1 negative clinical outcome post-index (usually cirrhosis). Conclusion: Results of this US population-based study demonstrate a potential unmet need for early intervention and effective treatment options for patients with PBC, as one in three patients with PBC remain untreated years after diagnosis.